Recent advances in high-performance millimeter-Wave acoustic resonators and filters using thin-film lithium niobate - Lu, Ruochen (Progress in quantum electronics, 2025)
This paper reviews recent advances in millimeter-wave (mmWave) piezoelectric acoustic resonators and filters, based on thin-film lithium niobate (LN) platforms. Recent utilization of transferred thin-film LN (TFLN) on various substrates has enabled high-performance microelectromechanical systems (MEMS) devices. For mmWave applications, TFLN supports an assortment of acoustic modes with large electromechanical coupling (k2), high quality factors (Q), and great frequency scalability. These features have led to significant recent performance enhancements in low-loss and wideband resonators and filters using TFLN. More specifically, acoustic resonators between 18 and 100 GHz have been demonstrated with low loss, compact form factors, and strong piezoelectric coupling. Acoustic filters have also been shown at mmWave frequency ranges, beyond the conventional sub-6 GHz operating range, toward addressing the stringent demands of future wireless communication systems. The review starts by analyzing the background and challenges of frequency scaling incumbent acoustic technologies, then introduces the unique potentials of TFLN platforms for mmWave resonator applications, highlighting fabrication techniques and novel device architecture. Beyond this, periodically poled piezoelectric film (P3F) LN is highlighted. The multi-layer structure with alternating orientations in adjacent layers enables high figure of merit (FoM = k2∙Q) acoustic devices at mmWave, efficiently coupling electrical and mechanical energy while minimizing damping in thicker film stacks. Finally, mmWave acoustic filter implementations have been reviewed and followed by outlooks for future work in mmWave acoustics.